2012
DOI: 10.1371/journal.pone.0046634
|View full text |Cite
|
Sign up to set email alerts
|

HCV NS5A Protein Containing Potential Ligands for Both Src Homology 2 and 3 Domains Enhances Autophosphorylation of Src Family Kinase Fyn in B Cells

Abstract: Hepatitis C virus (HCV) infects B lymphocytes and induces mixed cryoglobulinemia and B cell non-Hodgkin's lymphoma. The molecular mechanism for the pathogenesis of HCV infection-mediated B cell disorders remains obscure. To identify the possible role for HCV nonstructural 5A (NS5A) protein in B cells, we generated the stable B cell lines expressing Myc-His tagged NS5A. Immunoprecipitation study in the presence or absence of pervanadate (PV) implied that NS5A was tyrosine phosphorylated by pervanadate (PV) trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…A recent study has shown that casein kinase I is also involved in HCV particle assembly through NS5A hyperphosphorylation (25). In addi-tion to serine and threonine phosphorylation, we have reported that overexpressed NS5A is tyrosine-phosphorylated in response to treatment with pervanadate, an inhibitor of protein tyrosine phosphatases (26). Moreover, we and others have reported that NS5A binds to non-receptor protein-tyrosine kinases such as c-Src, Fyn, Syk, and c-Abl in vitro (26 -28).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…A recent study has shown that casein kinase I is also involved in HCV particle assembly through NS5A hyperphosphorylation (25). In addi-tion to serine and threonine phosphorylation, we have reported that overexpressed NS5A is tyrosine-phosphorylated in response to treatment with pervanadate, an inhibitor of protein tyrosine phosphatases (26). Moreover, we and others have reported that NS5A binds to non-receptor protein-tyrosine kinases such as c-Src, Fyn, Syk, and c-Abl in vitro (26 -28).…”
mentioning
confidence: 96%
“…-We have previously reported that the SH3 domain of c-Abl binds to NS5A in vitro and that overexpressed NS5A is tyrosine-phosphorylated in response to pervanadate treatment (26). We therefore investigated the possibility that c-Abl promotes HCV particle assembly by phosphorylating NS5A.…”
mentioning
confidence: 99%
“…c-Yes, a member of this family, is required for transportation of virions through the secretory pathway [ 76 ]. Several of the Src kinase family members are activated by HIV Nef [ 77 ], and also HCV NS5A induces phosphorylation events in the Src family [ 78 - 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…In some experiments, prepared cell lysates were subjected to pull-down assays for analysing tyrosine phosphorylation of 3BP2 induced by the cross-linking of FcγRI. Pull-down assays using GST-Abl-SH3 (residues between 84 to 138 of mouse c-Abl) were performed as described previously 14 , 56 .…”
Section: Methodsmentioning
confidence: 99%